Was Keynes a liberal or a socialist? - Matías Vernengo (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2023)
Right-wing critics of Keynes have often suggested that he was a socialist. His policy proposals were very often described as a slippery slope that would lead society into a totalitarian nightmare. Alternatively, from the left, Keynes was often seen as a reformist that intended to preserve the essence of capitalism. His reforms were mere window dressing on an exploitative system. The scholarship on Keynes also remained divided. However, in the last few decades a more robust position in favor of Keynes' socialist affiliation was developed, particularly in the careful scholarship by Rod O'Donnell and James Crotty. This paper suggests that while Keynes was a pragmatist willing to experiment in economic policy, and fully aware of the need to transform and transcend laissez-faire capitalism, he remained a liberal, in particular because Labourites, and most socialists, remained conservative in their economic policy outlook. Keynes was a revolutionary in economic theory, but a moderate in his politics.
Keywords: B13; B14; B22; B31; 330; Neoclassical Economics; Socialism; Macroeconomics; Keynes